Radiation Exposure of Ovarian Cancer Patients: Contribution of CT Examinations Performed on Different MDCT (16 and 64 Slices) Scanners and Image Quality Evaluation. Issue 17 (May 2015) - Rizzo, Stefania; Origgi, Daniela; Brambilla, Sarah; De Maria, Federica; Foà, Riccardo; Raimondi, Sara; Colombo, Nicoletta; Bellomi, Massimo
Abstract : Abstract: The objective of this study is to compare radiation doses given to ovarian cancer patients by different computed tomographies (CTs) and to evaluate association between doses and subjective and objective image quality. CT examinations included were performed either on a 16-slice CT, equipped with automatic z -axis tube current modulation, or on a 64-slice CT, equipped with z -axis, xy -axis modulation, and adaptive statistical iterative algorithm (ASIR). Evaluation of dose included the following dose descriptors: volumetric CT dose index (CTDIvol ), dose length product (DLP), and effective dose (E). Objective image noise was evaluated in abdominal aorta and liver. Subjective image quality was evaluated by assessment of image noise, spatial resolution and diagnostic acceptability. Mean and median CTDIvol, DLP, and E; correlation between CTDIvol and DLP and patients' weight; comparison of objective noise for the 2 scanners; association between dose descriptors and subjective image quality. The 64-slice CT delivered to patients 24.5% lower dose ( P < 0.0001) than 16-slice CT. There was a significant correlation between all dose descriptors (CTDIvol, DLP, E) and weight ( P < 0.0001). Objective noise was comparable for the 2 CT scanners. There was a significant correlation between dose descriptors and image noise for the 64-slice CT, and between dose descriptors and spatial resolution for the 16-slice CT. Current dose reduction systems may reduce radiation dose without significantly affecting image quality and diagnostic acceptability of CT exams.